Prospect of Pongamia pinnata (Karanja) in Bangladesh: A Sustainable Source of Liquid Fuel - Halder, P. K.; Paul, N.; Beg, M. R. A. (Journal of Renewable Energy, 2014)
Energy is the basic requirement for the existence of human being in today’s digital world. Indigenous energy of Bangladesh (especially natural gas and diesel) is basically used in power generation and depleting hastily to meet the increasing power demand. Therefore, special emphasis has been given to produce alternative liquid fuel worldwide to overcome the crisis of diesel. Pongamia pinnata (karanja) may be an emerging option for providing biooil for biodiesel production. Although karanja biooil has been used as a source of traditional medicines in Bangladesh, it can also be used for rural illumination. This paper outlines the medical and energy aspects of Pongamia pinnata. It has been assessed that Bangladesh can utilize about 128.95 PJ through Pongamia cultivation in unused lands. The paper reviews the potentiality of Pongamia pinnata as a source of biodiesel and its benefits in Bangladesh. The paper also revives that, about 0.52 million tons of biodiesel can be produced only utilizing the unused lands per year in sustainable basis as it reduces CO2, CO, HC, and NOx emission compared to pure diesel.